1996
DOI: 10.1136/thx.51.9.944
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of tuberculosis: the reverse of other respiratory diseases in the UK.

Abstract: Background -In Western societies there is a winter peak in mortality, largely accounted for by respiratory and cardiovascular deaths. In view of the known seasonal variation in vitamin D, and of the postulated link between tuberculosis and vitamin D deficiency, a study was undertaken to examine whether the presentation of tuberculosis had the same seasonal rhythm as other pulmonary infections. Methods -Using cosinor analysis the presence or absence of seasonality was determined for 57 313 tuberculosis notifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 8 publications
(3 reference statements)
5
86
1
Order By: Relevance
“…We have also shown that in vivo vitamin D supplementation enhances immunity to mycobacteria both in healthy people (10) and in a genetically defined subgroup of patients with active TB (11). Reports of seasonal variation in the prevalence of vitamin D deficiency (12) and TB incidence (13) in the United Kingdom provide further evidence that low vitamin D status may compromise antimycobacterial immunity in this setting.…”
Section: Vitamin D Deficiency (Serum 25-hydroxyvitamin D [25(oh)d] <50mentioning
confidence: 58%
“…We have also shown that in vivo vitamin D supplementation enhances immunity to mycobacteria both in healthy people (10) and in a genetically defined subgroup of patients with active TB (11). Reports of seasonal variation in the prevalence of vitamin D deficiency (12) and TB incidence (13) in the United Kingdom provide further evidence that low vitamin D status may compromise antimycobacterial immunity in this setting.…”
Section: Vitamin D Deficiency (Serum 25-hydroxyvitamin D [25(oh)d] <50mentioning
confidence: 58%
“…Europe-and South Africa for childhood tuberculous meningitis-have reported seasonal variation in tuberculosis incidence. [1][2][3] Older texts refer to historical seasonal fluctuations in tuberculosis mortality in the Americas. 4 However, no previous studies have described tuberculosis seasonality in Asia, to our knowledge.…”
Section: Seasonality Of Tuberculosis In India: Is It Real and What Domentioning
confidence: 99%
“…Reviewing and identifying temporal changes and the seasonal pattern of TB, especially among migrant population is of great importance. As seasonal patterns are recognized, we can take action to estimate future health problems appropriately, develop, and improve effective public health programs, determine goals, and make more effective use of available resources (15). Season may affect the mechanism of disease transmission and detection in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, season reflects when registration of disease is high thus, suitable programming can be provided (16)(17)(18). It has been proven that the incidence of most respiratory infections has seasonal changes and this seasonal pattern has been confirmed in most studies that have examined the seasonal pattern of TB incidence (15,(17)(18)(19)(20)(21)(22)(23)(24)(25). However, there is little documentation regarding the seasonal pattern of TB among emigrant populations.…”
Section: Introductionmentioning
confidence: 99%